Public Relations and Sustainable Development in Question in French Academic Works - Bouzon, Arlette (2011)
The needs to inform and convince are millenniums and part of any organized life. Due to the very nature of its activities in the economic and social sphere, and because the “Know-How” is no longer possible without the “Make-Known”, the organization (generally companies, associations, the public sector) has turned itself into a communication agent.